Early Enteral Nutrition in Mechanically Ventilated Patients With COVID‐19 Infection. (2nd March 2021) - Farina, Nicholas; Nordbeck, Sarah; Montgomery, Michelle; Cordwin, Laura; Blair, Faith; Cherry‐Bukowiec, Jill; Kraft, Michael D.; Pleva, Melissa R.; Raymond, Erica
Abstract: Background: Nutrition therapy is essential in critically ill adults. Little is known about appropriate nutrition therapy in patients with severe coronavirus disease 2019 (COVID‐19) infection. Methods: This was a retrospective, observational study in adult patients with confirmed COVID‐19 infection receiving mechanical ventilation. Data regarding patient demographics and nutrition therapy were collected. Patients that received enteral nutrition within 24 hours of starting mechanical ventilation were compared with patients starting enteral nutrition later. The primary outcome was inpatient length of stay. Propensity score matching was conducted to control for baseline differences in patient groups. Results: One hundred fifty‐five patients were included in final analysis. Patients who received enteral nutrition within 24 hours received a significantly greater daily amount of calories (17.5 vs 15.2 kcal/kg, P = .015) and protein (1.04 vs 0.85 g/kg, P = .003). There was no difference in length of stay (18.5 vs 23.5 days, P = .37). The propensity score analysis included 100 patients. Following propensity scoring, significant differences in daily calorie (17.7 [4.6] vs 15.1 [5.1] kcal/kg/d, P = .009) and protein (1.03 [0.35] vs 0.86 [0.38] g/kg/d, P = .014) provision remained. No differences in length of stay or other outcomes were noted in the propensity score analysis. Conclusion: Initiation of enteral nutrition within 24 hours was not associated with improved outcomes in mechanically ventilated adults with COVID‐19. No harm was detected either. Future research should seek to clarify optimal timing of enteral nutrition initiation in patients with COVID‐19 who require mechanical ventilation.